Model kurikulum berasaskan taman buah-buahan dan sayur-sayuran berkhasiat untuk sekolah rendah Orang Asli / Siti Farhah A. Aziz - Siti Farhah, A. Aziz (2016)
The objective of this research is to develop a Garden Based Curriculum Model (GBCM) on Nutritious Fruits and Vegetables for Indigenous Primary Schools. This research is based on the Design and Developmental Research (DDR) method. Based on this method, three main phases are employed to shape the model. As for phase one or needs analysis on indigenous school children for a Garden Based Curriculum on nutritious fruits and vegetables, this was carried out by interviewing 12 school teachers experienced in teaching Semai ethnic indigenous school children. Phase two involving design and development which developed the curriculum model using Interpretive Structural Modelling (ISM) approach involves 11 experts from various related disciplines. Data interpretations are based on the position of an element from the aspects of Driving Power and Dependent Power. Phase three or usability evaluation was done by experimentation based on the developed model by testing it on a 37 standard five Semai indigenous students. Evaluations were based on the Stake Countenance of Educational Evaluation Model by semi-structured interviews with 10 indigenous school children (pre and post suitability). Selection was through purposive sampling based on the required criteria. Findings from phase one indicate that there is a need for developing a garden based curriculum on a nutritious fruits and vegetables for indigenous primary schools. While findings of phase two on developing a garden based Curriculum Model on nutritious fruits and vegetables comprises four (4) curriculum components including objectives, content, teaching method and activities and evaluation. The model that has been developed supported Social Cognitive Theory (SCT) in three aspects namely Personality, Behavior and Environment. Findings of the third phase indicate the suitability of a Garden Based Curriculum model on nutritious fruits and vegetables to be applied in indigenous primary schools. The development of a vi garden based curriculum model on nutritious fruits and vegetables has a major impact on fruit and vegetable consumption behavior among the indigenous school children.